The relationship between perceived leadership style and perceived stress on hospital employees - YENER, MÜJDELEN İPEK (ELSEVIER SCIENCE BV, 2015)
A good leadership is important for health care organizations' success like any other ones and it affects our lives deeply. In the light of this study conducted on hospital employees, who are always serving in difficult conditions, is aimed to determine what type of leadership style should be embraced to decrease the negative effects of stress on individuals. Study examined 312 nonprofit hospital employees in Istanbul in order to determine if an association exists between hospital employees' perceived leadership style and perceived stress. Perceived leadership was assessed with Multifactor Leadership Questionnaire (MLQ). Perceived stress of the participants was assessed by The Perceived Stress Scale (PSS). The aim of the quantitative study was to investigate whether, and to what extent, relationship existed between perceived stress and perceived leadership style of hospital employees in Istanbul Turkey. The gathered data analyzed with statistical package software (SPSS). Results showed that between perceived leadership styles and perceived stress have a partial relationship. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Perceived Stress; Perceived Leadership Styles; Hospital employee